Ustekinumab dose escalation improves clinical responses in refractory Crohn's disease. (October 2020) - Haider, Syedreza A.; Yadav, Abhijeet; Perry, Courtney; Su, Leon; Akanbi, Olalekan; Kudaravalli, Praneeth; Tripathi, Nishant; Hashim, Mahmoud A.; Abdelsalam, Mohammed; Hussein, Mohamed; Elkheshen, Ahmed; Patel, Vihang; et al.
Background: Clinicians often utilize off-label dose escalation of ustekinumab (UST) in Crohn's disease (CD) patients with disease refractory to standard dosing. Previous studies report mixed results with dose escalation of UST. Methods: A retrospective observational study of 143 adult patients with CD receiving UST over a 33-month time period was conducted. Patients receiving UST at standard dosage for a minimum of 16 weeks were included in the analysis. Primary outcomes collected were clinical response [Physician Global Assessment Score (PGA) by >1] and remission (PGA = 0). Changes in clinical parameters were calculated for dose-escalated patients beginning with the time of dose switch (~42 weeks) and compared with a group of patients who were classified as "failing" standard dosing at 42 weeks who were not dose escalated. Results: Dose escalation improved PGA by 0.47 ± 0.19 compared with patients remaining on every 8 weeks dosing (Q8 week), who worsened by 0.23 ± 0.23 ( p  < 0.05). Dose escalation decreased CRP 0.33 ± 0.19 mg/L and increased serum albumin 0.23 ± 0.06 g/dL ( p  < 0.05). Surprisingly, disease duration and prior CD surgeries inversely correlated with the need for dose escalation. Conclusion: Our results support UST Q4 week dose escalation for selected CD patients who fail to achieve remission on standard Q8 week dosing. Dose escalation improves clinical outcomes, prevents worsening disease severity, and positively impacts CRP and albumin levels. Together these data indicate that clinicians should attempt Q4 week UST dosing in refractory CD patients before switching to an alternative class of biologic therapy.